Pendidikan Dasar Manajemen Administrasi dalam Memberikan Layanan Bermutu Bagi Santri di Pondok Pesantren Moderat At-Thohiriyah Pelamunan Banten - Akhmad Fauzi Hamzah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The community service program on basic administrative management education at Pondok Pesantren Moderat At-Thohiriyah Pelamunan Banten is a strategic response to the need for improving the quality of educational services in the era of Society 5.0. Conducted over two months (July–August 2024) using a Participatory Action Research (PAR) approach, the program involved various stages including participatory field surveys, Focus Group Discussions (FGDs), development of workshop materials, and the implementation of administrative management workshops focusing on budget management and organizational program planning. The program significantly enhanced the administrative management capacity of student organizations, evidenced by participants’ improved ability to develop priority-based work plans with accurate budget estimates. In addition to strengthening the professionalism of pesantren governance, the program fostered a collaborative and participatory work culture that contributed to the development of leadership, independence, and a sense of responsibility among students as future leaders of the ummah